Translatio Studiorum: Traslado de los libros y diálogo de las civilizaciones en la Edad Media - León Florido, F. (Revista General de Información y Documentación, 2006)
The purpose of this paper is to sketch the cultural and philosophical travel, the translation of the books and the knowledge, that covered many areas and many histories in the Middle Ages, that is called translatio studiorum. This travel covered long distances, spent time in diferent places and stablished a complex netwok of relations between peoples, cultures and civilizations all along the shores of the Mare Nostrum. The history of ideas claims to re-establish the acknowledge of the forgotten legacy from Arabian, Byzantin and Jewis traditions for the modern Western culture.
Keywords: Translatio studiorum; Medieval culture; Dialogue of civilizations; Arab tradition; Reception of the greek philosophy; Neoplatonism